Do siblings free-ride in "being there" for parents? - Shiko Maruyama; Meliyanni Johar (Quantitative Economics, 2017)
There is a potential free-rider problem when several siblings consider future provision of care for their elderly parents. Siblings can commit to not providing long- term support by living far away. If location decisions are made by birth order, older siblings may enjoy a first-mover advantage. We study siblings' location decisions relative to their parents by estimating a sequential participation game for U.S. data. We find (i) limited strategic behavior, that is, in two-child families, more than 92% of children have a dominant strategy, and (ii) a nonnegligible public good problem, that is, in families with multiple children, 18.3% more parents would have had at least one child living nearby had location decisions been made cooperatively.
Keywords: C72; D13; D62; D64; 330; Public goods; empirical game; informal care; free-riding; sequential participation game; first-mover advantage; prisoners' dilemma